3D Land Administration in line with the Spatial Development Lifecycle - Kalogianni, Eftychia (A+BE | Architecture and the Built Environment, 2025)
Land administration (LA) is a cornerstone of sustainable development, environmental management, and inclusive governance. Yet, many Land Administration Systems (LASs) remain fragmented and technologically outdated, limiting their capacity to meet rapid urbanisation, informal tenure, and increasing demands for transparent, data-driven decision-making. Over the past decades, substantial research has been undertaken and prototypes developed for 3D LA solutions. The advantages of such approaches are well recognised: they provide greater legal certainty, enable more accurate property valuation, and establish a robust foundation for 3D spatial planning. Nevertheless, widespread implementation has not yet materialised, largely because the concept has been regarded as impractical at national scale. This dissertation investigates how 3D LA can be integrated into the wider Spatial Development Lifecycle, emphasising on data reuse, interoperability and alignment with international standards. It also investigates how legal, technical, and organisational dimensions of LA can converge with emerging technologies, including Building Information Model, crowdsourced surveys, and high-accuracy positioning. The key contributions include: an international standardised cadastral survey information model; an international standards’ based cadastral survey workflow; a methodology for developing LADM-based country profiles; an international standardised 3D spatial profiles of varying complexity; a web-based 3D LA prototype; the introduction of the data lifecycle concept in 3D LA. Several of these concepts have been acknowledged by ISO and OGC and have already been adopted in LADM Edition II (ISO 19152-2:2025). This work provides practitioners, policymakers, and researchers with the tools and vision to advance innovative, transparent, and future-ready LASs.